A Critical Study on Work Attire for Female Medical Personnel in Regards to MUI Decree Number 4 of 2009 - Daud, Zakiul Fuady Muhammad; Rusuli, Izzatur; Fata, Ahmad Khoirul (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2025)
Covering the entire body except for the face and palms is the rule of aurat for Muslim women according to Islam, that aimed at preserving their dignity and honour. However, certain professions require Muslim women to expose some of their forearms, leading to the issuance of a decree by the Indonesian Ulema Council (MUI) regarding its permissibility. This paper aims to critically analyse the MUI decree on the attire of female medical personnel and provide alternative solutions to ensure that they do not expose any part of their aurat. This paper is a literature review utilizing content analysis. The findings of this paper indicate that the MUI decree number 4 concerning the attire of female medical personnel in 2009 contains two decisions: one regarding the ideal coverage of aurat for women and another regarding the permissibility of exposing some parts of the aurat during duty. The Sharia objectives contained in the first decision are aimed at preserving religion and life, while those in the second decision are aimed at safeguarding life and property. A solution to prevent female medical personnel from exposing their forearms is by using long sleeves or gloves. The implication of this paper is that MUI is expected to provide alternative options to maintain aurat in any circumstance. AbstrakMenutup seluruh tubuh kecuali wajah dan telapak tangan adalah aturan aurat bagi perempuan Muslimah menurut Islam dalam rangka menjaga kemuliaan dan kehormatannya. Namun demikian, dalam pekerjaan tertentu menuntut perempuan muslim untuk membuka sebagian lengannya sehingga MUI mengeluarkan fatwa tentang kebolehannya. Tulisan ini bertujuan untuk menganalisis secara kritis fatwa MUI tentang pakaian tenaga medis perempuan dan memberikan alternatif solusi agar tenaga medis tersebut tidak membuka sebagian auratnya. Tulisan ini merupakan kajian pustaka yang menggunakan analisis isi dalam analisanya. Hasil tulisan ini menunjukkan bahwa fatwa MUI nomor 4 tentang pakaian tenaga medis perempuan tahun 2009 mengandung dua putusan, yaitu tentang aurat perempuan yang seharusnya dan tentang kebolehan membuka Sebagian aurat ketika menjalankan tugas. Maqasid syariah yang terkandung pada putusan pertama adalah dalam rangka menjaga agama dan jiwa, sedangkan maqasid pada putusan kedua dalam rangka menjaga jiwa dan harta. Solusi yang bisa dilakukan agar tenaga medis perempuan tidak membuka sebagian lengannya adalah dengan menggunakan manset atau sarung tangan panjang. Implikasi dari tulisan ini adalah diharapkan MUI memberikan alternatif pilihan untuk tetap menjaga aurat dalam kondisi apa pun.